2016
DOI: 10.24925/turjaf.v4i8.676-683.681
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Sorption Isotherms of Yogurt Powder Containing Candied Chestnut Puree

Abstract: Yogurt powder was produced by freeze drying and with added candied chestnut puree at ratios of 5, 10, and 20 % by weight. Moisture sorption isotherms of yogurt powder samples, plain (YP), and containing 5, 10, 20% candied chestnut puree (CCP) were determined at 25°C using the standard, static-gravimetric method. The experimental adsorption data of yogurt powders at 25°C were fitted to 14 sorption equations which are most widely used to fit experimental sorption data of various food materials. The parameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The authors used the parameter of moisture to calculate the product shelf life, and concluded that moisture levels from 6.8% to 7.2% were decisive for product quality, since higher values led to particle agglomeration. In addition, it is worth mentioning that darkening is common under inadequate storage conditions, with the development of off-tastes due to the formation of insoluble compounds from the Maillard reaction (ZARE et al, 2011). Wang et al (2004) analysed soy yoghurt powder stored in glass, polyethylene terephthalate (PET) and laminated packages at 4 °C.…”
Section: Packaging and Stability Of Dehydrated Yoghurtsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors used the parameter of moisture to calculate the product shelf life, and concluded that moisture levels from 6.8% to 7.2% were decisive for product quality, since higher values led to particle agglomeration. In addition, it is worth mentioning that darkening is common under inadequate storage conditions, with the development of off-tastes due to the formation of insoluble compounds from the Maillard reaction (ZARE et al, 2011). Wang et al (2004) analysed soy yoghurt powder stored in glass, polyethylene terephthalate (PET) and laminated packages at 4 °C.…”
Section: Packaging and Stability Of Dehydrated Yoghurtsmentioning
confidence: 99%
“…Yoghurt powder could be used as an ingredient or supplement in juices, biscuits, ice cream, candies and milk beverages, besides replacing milk powder in recipes, hence adding nutritional and functional values to these products MISHRA, 2004b;TAMIME;ROBINSON, 2007;ZUNGUR BASTIOĞLU et al, 2016).…”
Section: Introductionmentioning
confidence: 99%